2002
DOI: 10.1088/0953-2048/15/4/307
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the TRUQ (Transformation-heat-based up-quenching) method for Nb3Al superconductors

Abstract: The newly developed transformation-heat-based up-quenching (TRUQ) process causes an improvement of the stoichiometry of the A15 Nb 3 Al phase and an enhancement of the high-field J c performance in Nb 3 Al superconductors. J c properties have been optimized in the fabrication steps for TRUQ Nb 3 Al superconductors. The TRUQ process in the vicinity of 1000 • C gives the best high-field and low-field J c 's as well as T c and B c2 . J c 's are not so sensitive to the holding time of the TRUQ process, which makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Samples 1-3 were annealed under the same conditions (800 for 10 h) to induce a phase transformation and long-range ordering. Sample 4 was deformed by 40% areal reduction, which is equivalent to that of sample 2, but the transformation was performed by annealing at a temperature of 1200 for 15 s (AR40-1200C) [14]. Sample 4 also requires post-annealing at 800 for 10 h to achieve long-range ordering of the phase; this process increases .…”
Section: A Samplesmentioning
confidence: 99%
“…Samples 1-3 were annealed under the same conditions (800 for 10 h) to induce a phase transformation and long-range ordering. Sample 4 was deformed by 40% areal reduction, which is equivalent to that of sample 2, but the transformation was performed by annealing at a temperature of 1200 for 15 s (AR40-1200C) [14]. Sample 4 also requires post-annealing at 800 for 10 h to achieve long-range ordering of the phase; this process increases .…”
Section: A Samplesmentioning
confidence: 99%
“…Transmission electron microscopy investigations have shown that this is due to local deviations from the stoichiometry, at the tens of nanometers scale, around certain Al-rich stacking faults formed during the transformation [21]. Three improved approaches have been developed to obtain better high field properties: the TRansformation-heat-based Up-Quenching method (TRUQ) [20], [22], the Double Rapid-Heating Quenching method (DRHQ) [24], and the Rapid Heating Quenching Ordering method (RHQO) [25], as summarized in Fig. 3 and Table II.…”
Section: Variants Of Rhqt Processmentioning
confidence: 99%
“…2 shows -characteristic of a short sample fabricated by TRUQ process at 1000 C for 1 min after the pre-heating at 600 C for 10 h, comparing with optimized performance of a TRUQ Nb Al short sample without pre-heating and a RHQT Nb Al sample. All the as-quenched bcc samples have same specifications listed in Table I and have been cold-worked by a drawing of 40% area reduction before the transformation heat treatment, so as to improve the performance [6]. As shown in Fig.…”
Section: A Influence Of Pre-heating Before Truq Processmentioning
confidence: 99%
“…The TRUQ process is a newly developed transformation technique to further improve the stoichiometry of the Nb Al phase, compared with the so-called rapid heating, quenching and transformation (RHQT) method [3]- [5]. Core of TRUQ Nb Al superconductors almost reaches 500 A/mm at 23.5 T and 2 K [6]. This value will be sufficient to satisfy the desired coil current density of a 1 GHz NMR magnet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation